Paths to victory : lessons from modern insurgencies - Paul, Christopher, 1971-; Clarke, Colin P.; Grill, Beth; Dunigan, Molly (Research report (Rand Corporation), 2013)
When a country is threatened by an insurgency, what efforts give its government the best chance of prevailing? Contemporary discourse on this subject is voluminous and often contentious. Advice for the counterinsurgent is often based on little more than common sense, a general understanding of history, or a handful of detailed examples, instead of a solid, systematically collected body of historical evidence. A 2010 RAND study challenged this trend with rigorous analyses of all 30 insurgencies that started and ended between 1978 and 2008. This update to that original study expanded the data set, adding 41 new cases and comparing all 71 insurgencies begun and completed worldwide since World War II. With many more cases to compare, the study was able to more rigorously test the previous findings and address critical questions that the earlier study could not. For example, it could examine the approaches that led counterinsurgency forces to prevail when an external actor was involved in the conflict. It was also able to address questions about timing and duration, such as which factors affect the duration of insurgencies and the durability of the resulting peace, as well as how long historical counterinsurgency forces had to engage in effective practices before they won.